2014
DOI: 10.11646/zootaxa.3793.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Mexican Grasshoppers: Liladownsia fraile, a new genus and species of Dactylotini (Acrididae: Melanoplinae) and an updated molecular phylogeny of Melanoplinae

Abstract: Liladownsia fraile gen. nov. sp. nov. Fontana, Mariño-Pérez, Woller & Song (Lila Downs' friar grasshopper) of the tribe Dactylotini (Orthoptera: Acrididae: Melanoplinae) is described from the pine-oak forest of the Sierra Madre del Sur Mountain Range in Oaxaca, Mexico. Taxonomic placement of this new genus is justified based on morphological characters as well as a molecular phylogeny. Information about the probable host plant, phenology, and known localities is also presented. We also present an updated molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 1,000 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In present trees, Dichroplini species were recovered as a monophyletic group, in agreement with the analysis of Chapco (2006) and Woller et al (2014). On the other hand, Chintauan-Marquier et al (2011) found the paraphyly of Dichroplini.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In present trees, Dichroplini species were recovered as a monophyletic group, in agreement with the analysis of Chapco (2006) and Woller et al (2014). On the other hand, Chintauan-Marquier et al (2011) found the paraphyly of Dichroplini.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies of Dactylotini including Hesperotettix viridis Thomas, 1872 discovered that this tribe is paraphyletic (Chapco 2006, Chintauan-Marquier et al 2011, Woller et al 2014. The prior analysis of the melanopline tribes placed Jivarini in a basal position in the subfamily (Amédégnato et al 2003, Woller et al 2014). In our results, Jivarini species were clustered together with Podismini representatives.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our total genetic dataset consisted of 1773 bp from three mitochondrial genes: protein‐coding cytochrome oxidase I (COI 633bp), cytochrome oxidase II (COII 393bp), and ribosomal coding (16S 424bp); and one nuclear fragment of the ribosomal internal transcribed spacer 2 (ITS‐2 323bp). Previous studies in Acrididae (Colombo et al ., ; Husemann et al ., ; Song et al ., ; Chintauan‐Marquier et al ., ; Woller et al ., ) have demonstrated that these molecular markers are informative and useful for comparison between species. Specific details on DNA extraction, PCR profiles, primers, and sequencing reactions can be found in Colombo et al .…”
Section: Methodsmentioning
confidence: 99%
“…). Although Ronderosia was recently included in the Scotussae genus group (Dinghi et al ., ), its phylogenetic relationships within the group is debatable (Colombo et al ., ; Chapco, ; Dinghi et al ., ; Woller et al ., ).…”
Section: Introductionmentioning
confidence: 97%